Ion mobility mass spectrometry and molecular dynamics simulations unravel the conformational stability of zinc metallothionein-2 species. Issue 30 (24th March 2023) - Peris-Díaz, Manuel David; Barkhanskiy, Alexey; Liggett, Ellen; Barran, Perdita; Krężel, Artur
Abstract : We present a molecular dynamics approach to explore the conformational landscape of proteins analyzed by ion mobility-mass spectrometry, providing new insights into the structural properties of metallothioneins, a cellular zinc buffer system. Abstract : Ion mobility-mass spectrometry (IM-MS) unraveled different conformational stability in Zn4–7 -metallothionein-2. We introduced a new molecular dynamics simulation approach that permitted the exploration of all of the conformational space confirming the experimental data, and revealed that not only the Zn–S bonds but also the α–β domain interactions modulate protein unfolding.